Effect of Blended Learning Method (Flex Model) on Final-Year Students of BAMS to Learn Shalyatantra - Pooja Shrivastav; Babaji Ghewade; Shweta Parwe; Sheetal Asutkar (Journal of Pharmacy and Bioallied Sciences)
Background: Blended learning is a blend of online and in-person instruction. This study was conducted to see its effect to learn Shalyatantra topic. Methodology: Final-year students (58) were equally in two groups. The topic was taught using a conventional technique in group A and a blended learning way in group B. Pre-test and post-test were conducted before and after the study, respectively. Students’ and teachers’ perceptions on Likert scale were also taken. Statistical analysis was done. Observation and Results: The mean post-test score of group B, i.e. blended learning group (18.37 ± 0.97), was more as compared to group A, i.e. conventional learning group (16.31 ± 1.53). Individually both groups were statistically significant. Conclusion: It can be concluded that blended learning helped in developing critical thinking, communication skill in students, and enhance the retention of course content.